2017
DOI: 10.1177/1756283x17702096
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided hepaticogastrostomy versus percutaneous transhepatic drainage for malignant biliary obstruction after failed endoscopic retrograde cholangiopancreatography: a retrospective expertise-based study from two centers

Abstract: Background:Percutaneous transhepatic biliary drainage (PTBD) is widely performed as a salvage procedure in patients with unresectable malignant obstruction of the common bile duct (CBD) after failed endoscopic retrograde cholangiopancreatography (ERCP) or in case of surgically altered anatomy. Endoscopic ultrasound-guided hepaticogastrostomy (EU-HGS) is a more recently introduced alternative to relieve malignant obstructive jaundice. The aim of this prospective observational study was to compare the outcome, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 34 publications
2
61
1
2
Order By: Relevance
“…Endoscopic ultrasound guided biliary drainage (EUS-BD) has been increasingly used as an alternative to percutaneous transhepatic biliary drainage after failed ERCP 2 3 . EUS-CD and EUS-HGS have been reported to have similar efficacity 4 .…”
Section: Case Reportmentioning
confidence: 99%
“…Endoscopic ultrasound guided biliary drainage (EUS-BD) has been increasingly used as an alternative to percutaneous transhepatic biliary drainage after failed ERCP 2 3 . EUS-CD and EUS-HGS have been reported to have similar efficacity 4 .…”
Section: Case Reportmentioning
confidence: 99%
“…3,4,7,8 A detailed description of the PTBD procedure was only reported in four out of six studies. 3,[5][6][7] PTBDs which were performed with ultrasound guidance had fewer adverse events (10-25%) than PTBDs which only used fluoroscopic guidance (31-46%). In the study from Artifon et al, 6 4 of the 12 patients underwent external drainage catheter insertion before metal stent implantation.…”
Section: Discussionmentioning
confidence: 99%
“…In the study from Sharaih et al, 8 it was not reported how many metal stents were inserted, and how many benign and malign diseases were mixed and not differentiated, which makes any comparison with EUS-BD very difficult. Lastly, in the study from Sportes et al, 7 the external drainage was left after metal stent implantation and removed some days later when stent implantation was clinically successful. This further procedure may not be necessary when stent release is visualized by endoscopic luminal guidance as discussed above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no significant difference in the overall technical success and safety of transhepatic or transduodenal access (42,43). In comparison to percutaneous biliary drainage EUS-BD has been shown in multiple studies to have higher clinical success rates, lower rates of adverse events and reintervention, along with lower hospital length of stay and costs (5,(44)(45)(46). When comparing EUS-BD to EA-ERCP in an international comparative study, the technical and success was higher for EUS-BD (98% vs. 65% and 88% vs. 59%), with shorter procedure times (55 vs. 95 min); although length of hospital stay and adverse events were more common in the EUS-BD (47,48).…”
Section: Eus-pbd: Current Evidencementioning
confidence: 99%